Intracranial Bleeding After Reperfusion Therapy in Acute Ischaemic Stroke Patients Randomized to Glyceryl Trinitrate vs. Control: An Individual Patient Data Meta-Analysis - Appleton, Jason P.; Woodhouse, Lisa J.; Sprigg, Nikola; Wardlaw, Joanna M.; Bath, Philip M. (Frontiers in Neurology, 2020)
Background: Thrombolysis, with or without thrombectomy, for acute ischaemic stroke is associated with an increased risk of intracranial bleeding. We assessed whether treatment with glyceryl trinitrate (GTN), a nitric oxide donor, may increase the associated bleeding risk. Methods: We searched for completed randomised controlled trials of GTN vs. no GTN in acute ischaemic stroke with data on reperfusion treatments (thrombolysis and/or thrombectomy). The primary efficacy outcome was functional status as assessed by the modified Rankin Scale (mRS) at day 90; the primary safety outcome was intracranial bleeding. Secondary safety outcomes included symptomatic intracranial haemorrhage and haemorrhagic transformation of infarction. Individual patient data were pooled and meta-analysis performed using ordinal or binary logistic regression with adjustment for trial and prognostic variables both overall and in those randomised within 6 hours of symptom onset. Results Three trials met the eligibility criteria. Of 715 patients with ischaemic stroke who underwent thrombolysis (709, >99%) or thrombectomy (24, 3.4%), 357 (49.9%) received GTN and 358 (50.1%) received no GTN. Overall, there was no difference in the distribution of the mRS at day 90 between GTN vs. no GTN (OR 0.94, 95% CI 0.72 to 1.23; p=0.65); similarly, there was no difference in intracranial haemorrhage rates between treatment groups (OR 0.90, 95% CI 0.3 to 1.89; p=0.77). In those randomised to GTN vs. no GTN within 6 hours of symptom onset, there were numerically fewer bleeding events, but these analyses did not reach statistical significance. Conclusions In ischaemic stroke patients treated predominantly with thrombolysis, transdermal GTN was safe, but did not influence functional outcome at 90 days.